2005
DOI: 10.1097/01.hjh.0000178834.26353.d5
|View full text |Cite
|
Sign up to set email alerts
|

Normative values for intima–media thickness and distensibility of large arteries in healthy adolescents

Abstract: Morphological and functional measures of large arteries should be normalized to take account of changes during adolescence and skewed distributions. Relative body mass, systolic blood pressure and/or pulse pressure are determinants of IMT and elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
247
5
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(290 citation statements)
references
References 50 publications
31
247
5
7
Order By: Relevance
“…The arterial stiffening as well as the IMT have shown to be associated with increased morbidity and mortality 38,39 . Recently, studies showing a correlation between SAH and PP observed in infancy and adolescence and the presence of arterial stiffening and IMT in young adults have been published [40][41][42][43] , indicating that the processes identifi ed in the elderly are also present in younger individuals. Studies with healthy young adults of both sexes also showed that the intima-media thickening (IMT) and aortic stiffening seem to refl ect two different entities of vascular damage, with IMT alone being associated to LDL-cholesterol and BMI 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The arterial stiffening as well as the IMT have shown to be associated with increased morbidity and mortality 38,39 . Recently, studies showing a correlation between SAH and PP observed in infancy and adolescence and the presence of arterial stiffening and IMT in young adults have been published [40][41][42][43] , indicating that the processes identifi ed in the elderly are also present in younger individuals. Studies with healthy young adults of both sexes also showed that the intima-media thickening (IMT) and aortic stiffening seem to refl ect two different entities of vascular damage, with IMT alone being associated to LDL-cholesterol and BMI 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with underlying vasculitis, diabetes, uncontrolled hyperlipidemia (serum cholesterol Ն5 mMol/L despite statin therapy), uncontrolled hypertension (systolic BP Ն95th centile for age despite therapy), and smokers were excluded. Because vascular measures are age dependent and normative data are available only for children who were older than 10 yr, 38 we compared our patient group with 40 age-and gendermatched healthy control subjects who were studied contemporaneously.…”
Section: Methodsmentioning
confidence: 99%
“…During the last decade, multiple reports have been published that support using cIMT and PWV measurements to evaluate target organ damage, and pediatric reference values for cIMT and PWV have been published (Table V and VI) [37][38][39][40][41][42]. These tests are already recommended (ESH 2016) as additional in the assessment of target organ damage in children with AH.…”
Section: Non-obligatory Additional Tests To Evaluate the Extent Of Tamentioning
confidence: 99%